Graphene-based four-corner meandered slotted THz antenna design for 6G/TWPAN high speed wireless communication devices - Ammar Armghan; Shobhit K. Patel; Sunil Lavadiya; Khaled Aliqab; Meshari Alsharari (Ain Shams Engineering Journal, 2025)
Fast-speed communication requires an antenna that works on high bandwidth gain. The graphene material has extraordinary properties, and we have utilised these properties to improve the antenna results to apply to wireless communication devices. We first presented a single-element graphene patch antenna, which gives high bandwidth and gain of 45THz and 10.8 dBi, respectively. The graphene patch design has a compact size of 68 × 68 µm2. The design gains are further enhanced using a two-port graphene MIMO antenna design for 14 dBi. The MIMO antenna diversity parameter analysis is also presented in the manuscript. The parametric analysis for the graphene thickness is also presented. The Electric field and current field analysis are presented in the manuscript. The designed antenna has high gain and ultra-broad bandwidth. The designed graphene MIMO antenna is applicable for 6G wireless communication devices and THz wireless personal area networks.